Work Discipline of Employees of the Library and Archives Service of Bengkulu Province - Putri, Salsahbilah; Saputra, Harius Eko; Rikardo, Yanuar (Social Sciences Journal, 2025)
This study aims to analyze the level of work discipline among employees at the Library and Archives Service of Bengkulu Province and identify the influencing factors. Work discipline is a crucial component in achieving organizational goals, particularly in government institutions that provide public information and archival services. The research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants consisted of institutional employees and library service users. The findings indicate that most employees demonstrate good discipline, especially in terms of attendance, compliance with regulations, and ethical behavior at work. However, some minor disciplinary issues were observed, such as the use of personal gadgets during working hours and loud conversations that disrupt the work environment. Factors affecting work discipline include leadership, electronic attendance systems, individual awareness, and the overall work environment. The study recommends continuous coaching, capacity-building for employees, and optimization of supervisory systems to enhance discipline and professionalism in the workplace.